Expression, prognosis and preliminary investigation of the mechanism of action of ACTR6, a member of the ARPs gene family, in hepatocellular carcinoma - Wang, Jing; Song, Meng; Tang, Jinming; Yue, Haoran; Guo, Xiaoyang; Chen, Zhan; Shen, Xiaolan; Cao, Mingbo (Frontiers in Medicine, 2025)
BackgroundHepatocellular carcinoma (HCC) is the third most prevalent cause of cancer-related mortality globally and the sixth most common cancer overall. It is critical to investigate new biomarkers and prognostic variables because there are currently no early diagnostic indicators. Actin-related proteins (ARPs) are involved in transcriptional regulation, chromatin remodeling, and DNA repair—all processes that have been connected to the development of cancer. However, it’s still unclear how ARPs and HCC are related.MethodsThrough the examination of databases like The Cancer Genome Atlas (TCGA) and The International Cancer Genome Consortium (ICGC), we examined the variations in the expression of ARPs between the transcriptomes of normal tissue and HCC. Furthermore, univariate and multivariate Cox analysis were used to assess the prognostic effects of ARPs. The investigation of immune cell infiltration and possible functional enrichment followed. Additionally, tissue chips containing regional liver cancer specimens were used to confirm ACTR6 expression and the clinical impact of prognosis using an immunohistochemistry (IHC) test. Finally, to investigate the expression and function of ACTR6 in liver cancer cells, real-time qPCR (RT-qPCR) assays, CCK-8, clone creation, cell cycle, and transwell migration and invasion experiments were carried out.ResultsWe found that, in addition to ACTR3C, 17 ARPs were significantly overexpressed in HCC compared with normal tissues. In both univariate and multivariate Cox models, ACTR6 and ACTL6A were identified as potential independent risk factors for the prognosis of HCC, with ACTR6 having the lowest p-value. Clinical samples also confirmed this conclusion. Furthermore, ACTR6 overexpression showed a strong connection with immune cell infiltration levels and clinical and pathological factors linked to a poor prognosis. Functionally, knocking down ACTR6 inhibited cell migration and proliferation, produced a G1 cell cycle arrest, and decreased the viability of liver cancer cells.ConclusionThese findings demonstrate that ACTR6 is highly expressed in HCC and is associated with poor prognosis. In addition, ACTR6 may induce immune cell infiltration and promote hepatocarcinogenesis by regulating the cell cycle.